Pengaruh Motivasi dan Stres Kerja Terhadap Kinerja Karyawan Dealer - Indah Sari Liza Lubis (Universitas Islam Sumatera Utara, 2021)
The aim of this article is to investigate the influence of work stress on employee motivation at CV. Aneka Teknik in Binjai city, to examine the impact of motivation on employee performance at CV. Aneka Teknik in Binjai city, and to explore the combined influence of work stress and motivation on employee performance at CV. Aneka Teknik in Binjai city. This research adopts a quantitative approach. The population consists of 25 (twenty-five) permanent employees at CV. ANEKA TEKNIK Binjai, and the researcher distributed questionnaires to all of them to gather data for analysis. The data obtained are numerical and are used to analyze the relationships between variables. Based on the partial analysis, the independent variable of Work Stress (X2) has a significant negative influence on the dependent variable of Employee Performance (Y) at CV. Aneka Teknik Binjai. However, based on the simultaneous analysis, the independent variable of Motivation (X1) does not have a significant influence on the dependent variable of Employee Performance (Y) at CV. Aneka Teknik. Nonetheless, the simultaneous analysis reveals that the independent variable of Work Stress (X2) has a significant influence on the dependent variable of Employee Performance (Y) at CV. Aneka Teknik Binjai.